THE INFLUENCE OF INNOVATIVE BEHAVIOR AND REWARD SYSTEM ON EMPLOYEE PERFORMANCE WITH CREATIVE THINKING ABILITY AS A MODERATOR - Liman, Ineh; Santamoko, Ruby; Limajatini, Limajatini; Anggraeni, Dian (Graduate Program of Universitas Tarumanagara, 2024)
In the effort to develop a company, having a strong human resource base is crucial. Good employee performance is the primary asset that can execute and influence various operational aspects of the company. Companies should be able to foster employee potential by encouraging innovative thinking and providing rewards to motivate them to improve their performance. This research aims to analyze the influence of innovative behavior, reward systems, and creative thinking ability on employee performance. The study employs a survey method with a quantitative approach, collecting data from 142 respondents who are employees of an organization. Data analysis was conducted using Smart PLS 3, and Hair's method was used to determine the sample size and respondent results. The research findings indicate that innovative behavior and the reward system positively affect employee performance. Creative thinking ability acts as a moderating variable that strengthens the impact of innovative behavior on employee performance. This research has significant implications for organizations, highlighting the need to enhance innovative behavior, reward systems, and creative thinking to improve employee performance. In the corporate context, if a company aims to boost employee performance, it should enhance innovative behavior and reward systems with the moderation of creative thinking ability.